Analysis of Article 23 Income Tax Treatment for Heavy Equipment Rental with a Lessee-Borne Tax Clause - Intan Andrella Nalrirati; Ratna Septiyanti; Suhartina, Suhartina (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to identify the treatment of Article 23 Income Tax at Internship Company in accordance with applicable regulations. This research is descriptive, which is carried out by systematically collecting and presenting data on an actual problem, then the researcher will analyze it and draw conclusions based on the data presented in this study. Thus, the results of the research on the collection and calculation system of Article 23 Income Tax on heavy equipment rental transactions at Internship Company are in accordance with applicable regulations. And based on the data presented as a company with tax-free entrepreneur status, Internship Company has fulfilled its obligations as a Taxpayer. However, in the calculation of Article 23 Income Tax outside the rental price given to the lessee. Until Internship Company receives net income minus the deduction of Article 23 Income Tax which is the responsibility of the lessee. Thus, the tax administration system implemented at Internship Company is quite effective and in accordance with procedures so as to minimize the potential for errors and tax administration sanctions.